Length-weight relationship and condition factor for Prochilodus lineatus, an important commercial fish, in contrasting water-quality environments of the middle Tietê River basin, Southeast Brazil - Urbanski, Bruna Q. [UNESP] (2023)
This work was carried out in order to provide the length-weight relationship (LWR) and the allometric condition factor (Ka), as well as its correlation with limnological variables, for Prochilodus lineatus from the middle Tietê River basin. Fish were collected using gill nets in two rivers with contrasting environmental conditions, totaling 46 specimens in the highly polluted Tietê River, and 37 in the Peixe River, a relatively well-conserved tributary. Environmental measures were obtained concomitantly to the fish capture. The results showed an isometric growth (b = 3.00) for the fish from Tietê River and a positive allometric growth (b = 3.23) for the fish from Peixe River. The mean value of Ka was unexpectedly higher for the main river (Ka = 2.63) when compared to its tributary (Ka = 2.42), being statistically different from each other. This can be explained by the much higher availability of organic sediments in the main river, resulting from a long-term eutrophication process. Nevertheless, the positive and statistically significant correlations with dissolved oxygen, for both rivers, as well as significant negative correlations with electric conductivity, nitrogen and chlorophyll a for Tietê River, indicate the negative effects of the water quality deterioration on the fish condition factor. The work contributes to the expansion of knowledge about P. lineatus, the most important commercial fish of the middle Tietê River basin, which is severely impacted by unsustainable human actions.